2010
DOI: 10.3109/03009742.2010.517546
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of adalimumab treatment in Greek children with juvenile idiopathic arthritis

Abstract: AD was safe and efficacious during the study period in the majority of patients. However, vigilance is required for the early detection of severe and potentially fatal infections. AD may control recurrent uveitis and radiological progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 30 publications
2
19
0
8
Order By: Relevance
“…Furthermore, several different agents were shown to be safe in this patient population. Other studies have shown similarly reassuring results in regards to the safety of using high dose biologics [5,6] and we believe that additional study is needed to affirm this treatment approach in recalcitrant disease states. Despite the limitations acknowledged, we did observe improvement in this group of patients with serious disease or previously unresponsive to standard dose therapy.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Furthermore, several different agents were shown to be safe in this patient population. Other studies have shown similarly reassuring results in regards to the safety of using high dose biologics [5,6] and we believe that additional study is needed to affirm this treatment approach in recalcitrant disease states. Despite the limitations acknowledged, we did observe improvement in this group of patients with serious disease or previously unresponsive to standard dose therapy.…”
Section: Discussionsupporting
confidence: 60%
“…Treatment of these diseases has only relatively recently included the use of biologic response modifiers, in particular Tumor Necrosis Factor (TNF) inhibitors [2]. Previous studies have shown the safety and efficacy of biologics in the treatment of pediatric inflammatory diseases [3][4][5][6]. Recent studies have also shown that higher dose treatment can lead to improved responses in children with some refractory diseases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Наиболее часто регистрировались реакции в месте введения и инфузионные реакции, а также инфекции дыхательных путей, кожи и мочевыводящих путей [57,58].…”
Section: контроль леченияunclassified
“…Так, в американском регистре CARRA больных с ЮИА 65% пациентов с сЮИА получали анти-ФНО ␣-терапию [48]; согласно греческому регистру, ада-лимумабом лечились 15% детей с сЮИА [49].…”
unclassified